Chinese Economy under Mao Zedong and Deng Xiaoping - Prof. Dr. Khalid Manzoor Butt; Sarah Sajid (Journal of Political Studies, 2018)
Economic development aims at building a healthy community which in turn strengthens institutions of a state. Economic Development can also be reflected through soft power, which is not only a diplomatic tool but also a booster for a state's attributed to Mao Zedong and the other to Deng Xiaoping. Mao and Deng have contributed to Chinese economic development by initiating compatible economic policies in their respective eras. Their economic policies are influenced by Karl Marx and Adam Smith respectivel strengthen the economy of China at the domestic level. On the other hand, Deng Xiaoping is associated with liberalizing of Chinese economy. The ideas of free trade and facilitation of foreign investors is the mainstay of Deng’s economic policy. In the process of liberalizing the Chinese economy, Deng initiated a paradigm shift from curtailed to liberal approach; he followed the footsteps of Adam Smith, the pioneer of free market economy. Privatization, establishment of exclusive economic zones, introduction of new flexible economic policies are the reforms introduced by Deng under the theory of free market economy. Hence, the modern China we see today is a product of the economic policies envisioned by these two great Chinese leaders. This descriptive research looks into the contribution and implication of these economic policies on the Chinese economic system.